Five-Year Long-Term Followup of a Primary Lymph node Gastrinoma: Is a Pancreaticoduodenectomy Justified? - Bernd Jaenigen; Gian Kayser; Berthold Steinke; Oliver Thomusch (Case Reports in Medicine)
Background. Gastrinoma-positive lymph nodes and failed localization of the primary tumor during surgical exploration are described. Specialists suppose that these lymph nodes are metastases rather than a primary gastrinoma. Methods. Case report with a five-year long-term followup. A 60-year-old patient with an confirmed gastrinoma was treated in our department. All preoperative evaluations including somatostatin-receptor-scintigraphy and F-Dopa PET failed to localize the gastrinoma. Explorative laparotomy revealed a gastrinoma in two peripancreatic lymph nodes. Despite extensive intraoperative exploration, no primary gastrinoma could be detected in typical localization. Results. Over a period of 5 years, the patient's gastrin level stayed in the normal range and the patient seems to be completely cured. Conclusion. A prophylactic partial pancreatoduodenectomy is not indicated to avoid recurrence, since complete biochemical cure by local resection of the lymph node gastrinoma is possible.